The Nordic Banking Crisis : Pitfalls in Financial Liberalization: Pitfalls in Financial Liberalization - Drees, Burkhard (Occasional Papers; Occasional Paper ;, 1998)
This study examines the banking crises in Finland, Norway and Sweden, which took place in the early 1990s, and draws some policy conclusions from their experiences. One key conclusion is that factors in addition to business cycle effects explain the Nordic countries financial problems. Although the timing of the deregulation in all three countries coincided with a strongly expansionary macroeconomic momentum, the main reasons for the banking crises were the delayed policy responses, the structural characteristics of the financial systems, and the banks inadequate internal risk-management controls.